Pedestrian satisfaction with aesthetic, attractiveness and pleasurability: evaluating the walkability of ChaharaghAbbasi Street in Isfahan, Iran - Rahimiashtiani, Zeinab; Ujang, Norsidah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2013)
Over the past decade the quality of the walking environment has become a significant factor in transportation planning and design in developed countries. It is argued that the pedestrians’ environment has been ignored in favour of automobile. Car dependency has reduced the quality of urban places, threatened their historical identity and changed the character and function of those places. ‘ChaharbaghAbbasi Street’, built in 1591 in Isfahan (Cultural Capital of the World of Islam in the year 2006), as the first green designed street in the Persian history and one of the pioneer recreational streets in the world, has been chosen in this study. Questionnaire surveys with 121 respondents were conducted to examine the walkability of ChaharbaghAbbasi Street based on identifiable criteria for walkable environment. Descriptive statistics were used to analyse the data. According to the findings, the pedestrians were not satisfied with the walkability of this street in general. However, they showed high positive satisfaction with aesthetics, attractiveness, and pleasurablity of the street. The findings will contribute to increasing the quality of the street as public space while maintaining the cultural-historical identity of the city. This can be achieved through operationalizing master plans for cities like Isfahan which will be beneficial both for the governmental and non-governmental organizations